Non food-related risk factors of campylobacteriosis in Canada: a matched case-control study. (December 2016) - Ravel, André; Pintar, Katarina; Nesbitt, Andrea; Pollari, Frank
Abstract Background Campylobacteriosis is a prominent bacterial gastrointestinal infection worldwide with several transmission pathways. Its non-foodborne routes have been less documented and quantified. The study aimed to quantitatively explore the role of potential risk factors not directly associated with food for sporadic cases ofC. jejuni infection in Canada. Methods This retrospective matched case-control study was built on an enhanced campylobacteriosis surveillance system and on a survey of healthy people and their behaviour with regards to potential risk factors for gastrointestinal infections that occurred in the same area in Canada. Eighty-five cases were individually matched by age and season to 170 controls. Results Through conditional logistic regression, risk factors were found only among water-related factors (drinking untreated water, using tap filter, drinking water from well and swimming in natural water), whereas drinking bottled water was protective. Among the 32 non-water related factors explored, 12 were surprisingly 'protective' factors without relevant explanation for that effect (for example gardening, attending a barbecue, eating food from a fast-food restaurant), suggesting that human infection byCampylobacter may be more frequently acquired at home than outside the home. Conclusions This study confirms and quantifies the importance of the waterborne transmission of campylobacteriosis. People are encouraged to drink only treated water and to avoid the ingestion of natural water as much as possible while swimming or playing in water. Globally, general hygiene and proper food handling and cooking practices at home should continue to be encouraged.